Comment - Szaszy, Mira (Victoria University of Wellington Law Review, 1995)
Dame Mira Szaszy provides a kaupapa from the past and present Presidents of the Māori Women’s Welfare League, which considers the role of Māori women in the negotiation and settlement of Treaty settlement claims. The author hopes that the voice of Māori women will be heard by all Māori and Pākehā, and that ownership is restored to the hapu and Iwi in the Treaty resolution process. However, the author argues that there are three fundamental problems with the Government’s then-proposed resolution process. First, it narrows the status and relevance of the Treaty. Secondly, it was created outside the spirit of the Treaty (the spirit of partnership). Thirdly, it will not restore Māori spiritual, social and economic ownership. The author criticises the general lack of genuine communication effort by all parties involved, arguing that the process has thrived on creating zones of exclusivity. The article concludes by introducing an alternative Treaty resolution process, which is found in this issue of the Victoria University of Wellington Law Review.